2004
DOI: 10.1086/381886
|View full text |Cite
|
Sign up to set email alerts
|

Drug‐Resistant Pneumococcal Pneumonia: Clinical Relevance and Related Factors

Abstract: A multicenter study of 638 cases of community-acquired pneumonia due to Streptococcus pneumoniae (SP-CAP) was performed to assess current levels of resistance. Of the pneumococcal strains, 35.7% had an minimum inhibitory concentration (MIC) of penicillin of > or =0.12 microg/mL (3 isolates had an MIC of 4 microg/mL), 23.8% had an MIC of erythromycin of 128 microg/mL, and 22.2% were multidrug resistant. Logistic regression determined that chronic pulmonary disease (odds ratio [OR], 1.44], human immunodeficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
76
3
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(93 citation statements)
references
References 43 publications
9
76
3
4
Order By: Relevance
“…Although none of our isolates was resistant to penicillin, 12.8% and 20% of our isolates respectively from blood culture and BAL specimens were found to be resistant to amoxicillin. We report that 48.7% and 60% of our isolates respectively from blood culture and BAL specimens were found to be resistant to erythromycin, which were higher than that reported (28%) elsewhere (40)(41)(42). The MIC 50 and MIC 90 of erythromycin against S. pneumoniae isolated from both blood culture and BAL specimens were 1 µg/mL and 64 µg/mL (range: ≤ 0.03 to > 128 µg/mL), respectively.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Although none of our isolates was resistant to penicillin, 12.8% and 20% of our isolates respectively from blood culture and BAL specimens were found to be resistant to amoxicillin. We report that 48.7% and 60% of our isolates respectively from blood culture and BAL specimens were found to be resistant to erythromycin, which were higher than that reported (28%) elsewhere (40)(41)(42). The MIC 50 and MIC 90 of erythromycin against S. pneumoniae isolated from both blood culture and BAL specimens were 1 µg/mL and 64 µg/mL (range: ≤ 0.03 to > 128 µg/mL), respectively.…”
Section: Discussioncontrasting
confidence: 49%
“…Erythromycin-resistant S. pneumoniae complicates the choice of antibiotic treatment since other macrolides such as clarithromycin and azithromycin might not be ideal choices where the prevalence of resistant pneumococci is high (38)(39)(40)(41)(42). We report an overall mortality of 9.9%, which is lower than that reported (30%) from France (43) reported that the local prevalence and bacterial resistance patterns determine the choice of first-line empiric therapy (44).…”
Section: Discussionmentioning
confidence: 66%
“…Patients and study design From January, 1999 to April, 2000, 638 consecutive adults with CAP-SP were enrolled in 35 Spanish hospitals [17]. A 30-day mortality, from the time of diagnosis, was considered the endpoint of the analysis [18].…”
Section: Methodsmentioning
confidence: 99%
“…In Spain, almost 40% of pneumococci strains express diminished susceptibilty to penicillin and approximately one-third of the isolates are macrolide resistant, most of them having macrolides lincosamides streptogramin-B phenotype [17]. The current authors, therefore, considered that Spain provides a good environment in which to respond to the previously mentioned controversies.…”
Section: European Respiratory Journalmentioning
confidence: 96%
See 1 more Smart Citation